Evaluation of Protective and Immunomodulatory Effects of Hydroalcoholic Extract of Scrophularia striata on Silver Nanoparticle-Induced Toxicity in Male Rats - Shamohammadi, Masoud; Pooyanmehr, Mehrdad; Maleki, Ali; Alimohammadi, Samad (Archives of Advances in Biosciences, 2021)
Introduction: Recently, silver nanoparticles (Ag-NPs) have found extensive and raising biomedical applications. Ag-NPs may lead to increased rate of toxicity on human health and environment. Because of the high antioxidant potential of the Scrophularia striata, the aim of the present study was to investigate the protective influence of Scrophularia striata against Ag-NPs-induced toxicity. Materials and Methods: Thirty male Wistar rats were randomly divided into 5 groups (n=6 for each group). Group 1 was normal control rats. Group 2 received only Ag-NPs (200 ppm). In groups 3 to 5, the rats were pretreated with different concentrations (20, 60 and 180 mg/kg) of the Scrophularia striata extract, respectively and then were treated with Ag-NPs to induce toxicity. Animals were treated once daily by gavage over a period of 30 days. At the end of the treatment period, blood samples were collected and serum IgG, IgM, C3, C4, and CRP levels were determined. Data were statistically analyzed through one-way ANOVA, followed by Tukey’s post hoc test. Results: Oral administration of Ag-NPs evoked a significant increase in the serum IgG, IgM, C3, C4, and CRP levels, compared with those in the control group (P<0.05). These changes were ameliorated through treatment with Scrophularia striata extract at different doses as compared with the Ag-NPs-treated group (P<0.05). Conclusion: The extract was found to be as an effective immunomodulatory agent against Ag-NPs-induced toxicity presumably due to its active compounds with medicinal value.